Urgensi Persetujuan Dewan Perwakilan Rakyat dalam Pengangkatan Jabatan Publik - Fany Krisdianto; Dodi Jaya (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Every country and every government, whatever its form and system of government, is required to design and implement policies that are appropriate to the socio-economic conditions of its people and are effective in directing the policies that must be implemented by government organs and government bureaucracy. decisions made by someone who has authority in government, both formal and informal. The approval of the House of Representatives (DPR) for appointments to public positions that are not regulated in the 1945 Constitution of the Republic of Indonesia is an important mechanism in the Indonesian constitutional system. Although the 1945 NRI Constitution does not regulate in detail all public positions, several derivative laws give the DPR the authority to approve the appointment of certain officials. This process is important to ensure checks and balances in government, prevent abuse of power by the executive, and increase accountability and transparency. Through an open fit and proper test, Constitutional Court Decision Number 16/PUU-XII/2014, I Request for re-examination regarding paragraphs (2) to (8) Article 30 of the Corruption Eradication Commission Law, Law concerning DPR Involvement in Recruitment Corruption Activities candidate for member of the Corruption Eradication Commission. Participating in filling public positions by the DPR is regulated by the 1945 Constitution of the Republic of Indonesia (1945 Constitution) and so on. The 1945 Constitution with its broad authority has its own objectives. This study seeks to understand how constitutional DPR protocols can assess the competence and integrity of candidates for public office, so that elected officials are able to carry out their duties well and receive legitimacy from the people. Thus, the DPR's involvement in this process strengthens democratic principles and improves the quality of government in Indonesia.